Handbook of polymer crystallization - Piorkowska, Ewa; Rutledge, Gregory Charles (Wiley, 2013)
"The only comprehensive reference on polymer crystallization, Handbook of Polymer Crystallization provides readers with a broad, in-depth guide on the subject, covering the numerous problems encountered during crystallization as well as solutions to resolve those problems to achieve the desired result."--Resumé vydavatele